Use of Dried Blood Spots to Elucidate Full-Length Transmitted/Founder HIV-1 Genomes - Jesus F. Salazar-Gonzalez (Pathogens and Immunity, 2016)
Background: Identification of HIV-1 genomes responsible for establishing clinical infection in newly infected individuals is fundamental to prevention and pathogenesis research. Processing, storage, and transportation of the clinical samples required to perform these virologic assays in resource-limited settings requires challenging venipuncture and cold chain logistics. Here, we validate the use of dried-blood spots (DBS) as a simple and convenient alternative to collecting and storing frozen plasma.